International survey on voice quality: Forensic practitioners versus voice therapists - Eugenia San Segundo (Estudios de Fonética Experimental)
In recent years, numerous investigations have focused on voice quality (VQ) for forensic purposes. These studies notwithstanding, we lack an international picture of how VQ is generally understood by forensic practitioners and how it contrasts with the practices of voice therapists. To fill this gap, a survey was designed and sent to both cohorts: forensicists and clinicians. A total of 45 responses from 20 countries were received. Important differences were found between groups, particularly regarding perceptual assessment. One conclusion to be drawn is that more emphasis should be placed on calibration and error measurement in forensic approaches to VQ. Further collaborations with clinicians should also be encouraged.